Porous Carbon as Anode Catalyst Support to Improve Borohydride Utilization in a Direct Borohydride Fuel Cell. Issue 2 (10th April 2015) - Li, G. R.; Wang, Q. Q.; Liu, B. H.; Li, Z. P.
Abstract Our study explores the use of porous carbon as anode catalyst support to improve borohydride utilization in a direct borohydride fuel cell. Pt catalysts supported by carbon aerogel (CA) and macroporous carbon (MPC) are synthesized by template method. The pores in porous carbon materials catch hydrogen bubbles to regulate the contact of anolyte with catalytic sites, and this leads to the depression of hydrogen evolution during BH4− electrooxidation. However, the hydrogen bubbles in the pores simultaneously deteriorate charge carrier transport and thus increase anode polarization. The CA‐supported Pt catalyst improves the coulombic efficiency of BH4− electrooxidation. However, the MPC‐supported Pt catalyst performed better than the CA‐supported Pt catalyst. MPC also has a good pore distribution, which improves the coulombic efficiency of BH4− electrooxidation without decreasing anode performance.